2006
DOI: 10.1074/jbc.m513667200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Human Centrin 2-Xeroderma Pigmentosum Group C Protein Complex

Abstract: Human centrin-2 plays a key role in centrosome function and stimulates nucleotide excision repair by binding to the xeroderma pigmentosum group C protein. To determine the structure of human centrin-2 and to develop an understanding of molecular interactions between centrin and xeroderma pigmentosum group C protein, we characterized the crystal structure of calcium-loaded full-length centrin-2 complexed with a xeroderma pigmentosum group C peptide. Our structure shows that the carboxyl-terminal domain of centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 55 publications
(54 reference statements)
11
118
0
Order By: Relevance
“…on April 7, 2019 by guest http://mcb.asm.org/ Similar structures have been identified in Kar1 and XPC/Rad4 (7,22,37,46,50). The interactions between Cdc31 and diverse cellular proteins were revealed in genetic studies (23) and are consistent with multiple roles.…”
supporting
confidence: 55%
“…on April 7, 2019 by guest http://mcb.asm.org/ Similar structures have been identified in Kar1 and XPC/Rad4 (7,22,37,46,50). The interactions between Cdc31 and diverse cellular proteins were revealed in genetic studies (23) and are consistent with multiple roles.…”
supporting
confidence: 55%
“…S1B, Left). This result is consistent with previous data showing that XPC and RAD23B interact in a 1:1 ratio (26) and that XPC and CETN2 also interact in a 1:1 ratio (27,28). Furthermore, a 1:1:1 stoichiometry is consistent with the size of the ∼200-kDa product we observe for the cross-linked complex (Fig.…”
Section: Resultssupporting
confidence: 82%
“…However, we also observed binding (albeit to a much lesser extent) of nonSUMOylated centrin-2 to XPC protein, in agreement with previous in vitro binding studies (Araki et al, 2001) and our notion that nuclear localization of centrin-2 was not completely abolished upon interference with the SUMOylation pathway. Structural studies using small peptides showed residues 847-863 of the XPC protein to associate with centrin-2 in vitro (Popescu et al, 2003;Thompson et al, 2006). However, these experiments did not address the posttranslational modifications on either XPC protein or centrin-2.…”
Section: Discussionmentioning
confidence: 93%